An automated railway system : railway network automation for Bangladesh railway - Imtiaz, Abir; Qazi Taskin Ibne Masud; Chowdhury, Zinia Faisal (BRAC University, 2015)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2014.